Review on the Application of Airborne LiDAR in Active Tectonics of China: Dushanzi Reverse Fault in the Northern Tian Shan - Sun, Wen; Wei, Zhanyu; Sun, Haoyue; He, Honglin (Frontiers in Earth Science, 2022)
High-resolution topographic data are fundamental for active tectonics studies. Within the last 2 decades, the airborne light detection and ranging (LiDAR) system provided a solution for the accurate and efficient acquisition of detailed geomorphic features. The use of LiDAR data for the identification of microstructural and geomorphic features, fault zone activity analysis, and earthquake disaster assessment remains challenging and has been the focus of active tectonics studies. Based on the LiDAR data of Dushanzi anticline – a reverse fault zone in Xinjiang, China, our group carried out a significant number of active tectonic research studies. By reviewing the specific content of these works, we summarized the main application of LiDAR for a specific structure, the Dushanzi Reverse Fault in the northern Tianshan. In addition, other applications of LiDAR in active tectonics are summarized in this paper. These studies show that high-resolution LiDAR data facilitate detailed studies of the fault activity and paleoseismicity. We hope more researchers can realize the advantages of LiDAR technology in active tectonics research and apply LiDAR technology into their own practical work, so as to promote the development of active tectonics research.